Evaluation of energy expenditure in the acute care of severe head injury patients : indirect calorimeter versus harris benedict formula - Saiful Razman, Mohd Noor (2008)
Management of comatose patients especially severely head-injured patients is very crucial due to the fact that secondary insult such as brain edema, hypo/hypertension, anemia and hypoxemia may develop during this period of time. Such patients are managed in intensive care units and usually need ventilatory support and further neurosurgical interventions. Apart from the medical and surgical aspects of management, nutritional support plays an important role in patient's recovery. There are few literatures on head-injured patients' energy requirement or expenditure in the acute setting (Clifton et al., 1986, Hadley et al., 1986, Michele et al., 2003 and Foley et al., 2008). Adequate energy supply for head-injured patients is an important part of intensive care management (ICU) in order to achieve optimal care and to avoid complications of hypo/hyper caloric feeding. It is believed that patients with different grades of head injury have different energy requirements and thus nutritional support both in the acute and chronic setting. By mean of an indirect calorimeter, we managed to measure the energy expenditure of severe head injury patients in an acute setting in the Neuro Intensive Care Unit, Hospital Universiti Sains Malaysia and compared the results to the predictive values obtained via Harris-Benedict Formula. We also managed to compare the difference of energy expenditure in the different grades of severity of head injury based on Marshall's classification system and compared the energy expenditure values amongst major operation, minor operation and conservative management groups. In this study, we also managed to determine the sensitivity and specificity of Harris-Benedict Formula as compared to the indirect calorimeter. Special interest was given to the analysis of twenty-four hour blood glucose levels and its association with severe head injury. This study is another step forward for better understanding in the management of critically ill patients in a tertiary neurosurgical center in Malaysia.